Roman frontier archaeology - in Britain and beyond : papers in honour of Paul Bidwell presented on the occasion of the 30th annual conference of the Arbeia Society - Bidwell, Paul T.,; Hodgson, Nick, Dr.,; Griffiths, Bill, (Archaeopress Roman archaeology ;, 2022)
Contributions by leading archaeologists and historians pay tribute to Paul Bidwell, admired for his ground-breaking work both in the south-west and the military north of Roman Britain. This collection will be essential reading for anyone with an interest in either the civil or military aspects of Roman Britain, or the frontiers of the Roman empire.